Qingda Granule Attenuates Angiotensin II-Induced Renal Apoptosis and Activation of the p53 Pathway - Long, Linzi; Zhang, Xiuli; Wen, Ying; Li, Jiapeng; Wei, Lihui; Cheng, Ying; Liu, Huixin; Chu, Jianfeng; Fang, Yi; Xie, Qiurong; Shen, Aling; Peng, Jun (Frontiers in Pharmacology, 2022)
Background: Qingda granule (QDG) exhibits anti-hypertension and multiple target organs protection. However, the therapeutic potential of QDG on hypertensive renal injury remain unknown. Therefore, the main objective of the current study is to explore the effects and underlying mechanisms of QDG treatment on renal injury in Ang II infused mice. Methods and results: Mice were infused with Angiotensin II (Ang II) (500 ng/kg /min) or saline for 4 weeks with subcutaneously implanted osmotic pumps. After infusion, mice in Ang II + QDG group were intragastrically administrated with QDG daily (1.145 g/kg/D), whereas the Control group and Ang II group were intragastrically administrated with same amount of double distilled water. Blood pressure of the mice monitor using CODA™ non-invasive blood pressure system revealed that QDG treatment significantly attenuated the elevated blood pressure. Moreover, hematoxylin-eosin staining indicated that QDG treatment ameliorated Ang II induced renal morphological changes, including glomerular sclerosis and atrophy, epithelial cells atrophy, and tubular dilatation.RNA-sequencing (RNA-seq) identified 662 differentially expressed transcripts (DETs) in renal tissues of Ang II infused mice, which were reversed after QDG treatment. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis based on DETs in both comparisons of Ang II vs. Control and Ang II+QDG vs. Ang II identified multiple enriched pathways, including apoptosis and P53 pathway. Consistently, terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling (TUNEL) staining and Annexin V staining revealed that QDG treatment significantly attenuated Ang II induced cell apoptosis in renal tissues and cultured renal tubular epithelial cells line (NRK-52E). Furthermore, western-blot analysis indicated that Ang II infusion significantly up-regulated the protein expression of p53, BCL2-associated X (BAX), cle-caspases-9 and cle-caspases-3 protein expression, while down-regulated the protein expression BCL-2 in renal tissues, which were attenuated after QDG treatment. Conclusion: Collectively, QDG treatment significantly attenuated hypertensive renal injury, partially by attenuating renal apoptosis and suppressing p53 pathways might be the underlying mechanisms.